PENGARUH ANIME NARUTO DAN MINAT BELAJAR MAHASISWA TINGKAT III PRODI PENDIDIKAN BAHASA JEPANG FKIP UNIVERSITAS RIAU - Katrin Helena; Hermandra Hermandra; Nursal Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research aims to describes the influence of anime and interest in learning at the level 3 students of Japanese language education at FKIP Riau University. This research aims to find out how much influence the Naruto Anime and Student Interest in Level III Japanese Language Education Study Program FKIP Riau University. In this research the authors used a descriptive qualitative research method. The data in this study were collected through a questionnaire that was used to measure the influence and interest in learning of third-level Japanese Language Education students at Riau University.Key Words: Influence, Anime, Interest In Learning